New technique for pediatric venous port implantation: Single incision double pocket technique - Umutoglu, Tank; Topuz, Ufuk; Bakan, Mefkur; KARAASLAN, Kazım; KARAASLAN, KAZIM; ÇAKIR, FATMA BETÜL; ÇAKIR, FATMA BETÜL; Orturk, Erdogan (My University, 2013)
Objective: In general intravenous access might be essential in patients with increased length of hospital stay for obtaining blood samples and for administration of intravenous fluid solutions, medications and total intravenous nutrition solutions. Extended length of use and repeated usage may worsen the peripheral intravenous access. In these conditions long term central venous catheters and implantable chest ports eases the clinicians- duty. With single incision double pocket technique, two subcutaneous pockets were done with surgical technique just above and below the incision; catheter was placed when the reservoir is in the upper pocket and then fixed at the lower pocket. We think that this technique will decrease the complications related with implantable chest ports placement in pediatric patients. In this study sigle incision double pocket technique was evaluated.